Effect of different stacking sequences on hybrid carbon/glass/epoxy composites laminate: Thermal, dynamic mechanical and long-term behavior - Silva Monte Vidal, Dielly Cavalcanti da [UNESP]; Ornaghi Jr, Heitor L. [UNESP]; Ornaghi, Felipe Gustavo [UNESP]; Monticeli, Francisco Maciel [UNESP]; Cornelis Voorwald, Herman Jacobus [UNESP]; Hilario Cioffi, Maria Odila [UNESP] (Sage Publications Ltd, 2019)
In the present study, different stacking sequences on hybrid carbon/glass/epoxy composites laminate were examined in relation to thermal, dynamic mechanical and long-term behavior. A positive hybrid effect was found for both hybrid composites (interleaved-Hybrid 1 and in block-Hybrid 2) showing that in some cases hybrid composites can properly replace carbon or glass composites. The composite containing all glass fiber in the middle (Hybrid 2) presented similar thermal behavior when compared to glass fiber composite. All hybrid composites presented higher storage modulus when compared to glass composite. Dynamic mechanical analysis showed that both hybrids can satisfactorily perform the requirement in a wide temperature range. The long-term prediction was successfully applied for all composites, showing to be highly temperature-dependent. Hence, depending on the application requirement, both hybrids can be used, saving weight and cost.
Keywords: Structural composites; stacking sequence; carbon fiber; long-term prediction